Antecedents of Work Outcomes of Local Government Employees: The Mediating Role of Public Service Motivation - Dwi Kristanti; Wayu Eko Yudiatmaja (Indonesian Association for Public Administration, 2022)
Many studies have analyzed the performance of government employees, but there is still little research on the relationship between equal employment opportunity and public service motivation. The purpose of this study was to examine whether equal employment opportunities affect individual job satisfaction and job performance. This study also evaluated whether the relationship is mediated by public service motivation. The survey research was implemented in the Bengkulu City Government to achieve the study objectives. There were 252 participants in this study who responded by completing an online questionnaire. The results of the structural equation modeling show that job satisfaction and individual job performance are equally influenced by job opportunities and public service motivation. In addition, the influence of equal employment opportunity on job satisfaction and individual job performance is mediated by public service motivation. The implications of this work on the theory and practice of human resource management in the public sector are outlined in the findings.